Subnational trends and inequalities of under-immunisation and zero-dose among children aged 12–23 months in Uganda: a national population-based cross-sectional study - Aluísio J D Barros; Peter Waiswa; Rornald Muhumuza Kananura; Jennifer Harris Requejo; Ronald Wasswa; Thiago M Santos (BMJ Open)
Objective Despite the Global Vaccine Action Plan’s goal of at least 90% vaccine coverage for all children, Uganda has made limited progress in vaccination over the past decade. The objective of this study was to examine the subnational trends in the prevalence and inequalities in under-immunisation and zero-dose among children aged 12–23 months in Uganda.Study design A retrospective national cross-sectional study.Setting UgandaParticipants Uganda Demographic and Health Survey secondary data of only children aged 12–23 months. The samples selected for analyses were 1507 in 2006, 1409 in 2011 and 2650 children in 2016.Outcome measure The primary outcomes were under-immunisation and zero-dose vaccination.Absolute and relative inequality measures were used in the analysis.Results From 2006 to 2016, the under-vaccination rate decreased by 21%, but remained high at 40.8%. The zero-dose vaccination rate dropped by 82%, affecting 1.2% of children in 2016. Subnational inequalities in under-vaccination increased over time with widening gaps between regions. While inequalities across wealth quintiles, maternal education levels and places of residence narrowed, children of mothers with lower education levels continued to have the highest under-vaccination rates. The rural–urban gap for zero-dose vaccination remained unchanged, with rural children disproportionately impacted.Conclusion While some progress was made in reducing under-vaccination rates in Uganda within the study period, no region achieved an under-vaccination rate below 20%. This indicates significant challenges in reaching the Sustainable Development Goal target of at least 80% immunisation coverage. Targeted interventions are necessary to improve healthcare access, enhance public health communication and strengthen the health system, particularly in underserved communities and among vulnerable populations.